PENGARUH PENGGUNAAN MEDIA SIMULASI JARINGAN CISCO PACKET TRACER TERHADAP HASIL BELAJAR SISWA - Fitri Eka Setia; Putra Jaya (Universitas Negeri Padang, 2019)
The purpose of this research is to find out the influence of student learning outcomes by applying learning using simulation media based on simulation using Cisco packet tracer with learning using power point as a learning medium in class XI network infrastructure administration subjects Computer and Network Engineering 3 Vocational School 3 Pariaman. This study uses pre-experimental design. The instruments used are objective questions for evaluating cognitive data and practicum data sheets on skills data assessment. Furthermore, analyzing the normality testing, homogeneity and hypothesis testing. Cognitive assessment obtained results of the average of value the experimental class 83 and the control class obtained results 79. While the skills assessment results obtained 93.5 in the experimental class and the control class scored 79. The influence of the percentage produced 4.6% on cognitive values and 15.6% assessed skills. Hypothesis calculation obtained 2,76 results> 1,69 in the experimental class and 8,19> 1,69 in the control class where the data was declared normal. It was concluded that the use of Cisco packet tracer network simulation media had an influence on student learning out comes. So, Cisco packet tracer network media simulation is more efficient to use than media that uses power point.Keywords: Learning Outcomes, Network Media Simulation, Cisco Packet Tracer